2014
DOI: 10.1080/17451000.2014.943240
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding for the identification of soft remains of prey in the stomach contents of grey seals (Halichoerus grypus) and harbour porpoises (Phocoena phocoena)

Abstract: In recent decades, grey seals (Halichoerus grypus) and harbour porpoises (Phocoena phocoena) have become more numerous along the coasts of Brittany in northwestern France. Their interactions with fisheries are of increasing concern and diet analyses are becoming a requirement to determine the actual overlap between species targeted by fisheries and marine mammal prey. However, as only a few stranded or by-caught animals are available to investigate the diet of these top predators, it is necessary to optimize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…However, the same sequences were obtained for duplicate subsamples showed that it was unlikely that the lack of detection of diet composition was due to the procedural errors. In addition, the universal CO I primers used in this study are able to amplify CO I gene fragments from 11 invertebrate phyla and fish [30], as shown in previous studies [38, 39]. A strong dietary preference probably played a decisive role in this result.…”
Section: Discussionsupporting
confidence: 60%
“…However, the same sequences were obtained for duplicate subsamples showed that it was unlikely that the lack of detection of diet composition was due to the procedural errors. In addition, the universal CO I primers used in this study are able to amplify CO I gene fragments from 11 invertebrate phyla and fish [30], as shown in previous studies [38, 39]. A strong dietary preference probably played a decisive role in this result.…”
Section: Discussionsupporting
confidence: 60%
“…Similarly, among often brittle and transparent gelatinous taxa, DNA barcodes increase the detectability of prey items previously difficult to score (Méheust et al 2015;Hauff et al 2015). …”
Section: Clarifying the Links Of Aquatic Food Websmentioning
confidence: 99%
“…In most cases, these studies build on one of two techniques: specific PCR primers designed to reveal predation on one or a few specific prey taxa, or the amplification of DNA using universal or group-specific primers as followed by sequencing of the amplicon. Diet studies of these types have been applied extensively to marine taxa ranging from higher trophic levels (e.g., Deagle et al 2005;Dunn et al 2010;Méheust et al 2015) through marine birds (e.g., Deagle et al 2007;Bowser et al 2013) and fish (e.g., Moran et al 2016) to different invertebrates and lower trophic levels (e.g., Jarman et al 2002;Nejstgaard et al 2003;Blankenship and Yayanos 2005;Leal et al 2014b;Olsen et al 2014;Hu et al 2015;reviewed in Calado and Leal 2015). DNA-based approaches have also yielded breakthrough dietary analyses in complex freshwater systems (e.g., Corse et al 2010;Carreon-Martinez et al 2011;Bartley et al 2015).…”
Section: Clarifying the Links Of Aquatic Food Websmentioning
confidence: 99%
“…Moreover, other studies have inspected the spatial differences in diet composition (Granquist et al, ; Thomas, Nelson, Lance, Deagle, & Trites, ) and investigated the seasonal variation in this seals' dietary habits (Voelker, ). The red lionfish, Adelie penguins, and the gray seal H. grypus were used in three different studies each, mostly for methodological purposes (Harms‐Tuohy et al, ; Jarman et al, , ; Parsons et al, ; Tverin et al, ), but also to investigate the species' foraging habits (Côté et al, ; Jarman et al, ; Méheust, Alfonsi, Le Ménec, Hassani, & Jung, ; Valdez‐Moreno et al, ). As such, all these species are good candidate models for future barcoding‐based dietary studies.…”
Section: Taxonomic and Geographical Bias In Terrestrial And Aquatic Mmentioning
confidence: 99%
“…On the other hand, among the 13 studies on interactions between humans and aquatic taxa, the majority focused on the pressure top predators, mostly seals, can exert on marine fisheries and/or on endangered fish (Granquist et al, ; Méheust et al, ; Purcell et al, ; Schwarz et al, ; Thomas et al, ; Tverin et al, ), or on the impacts of two invasive species, the lionfish on Caribbean coral reef ecosystems (Côté et al, ; Harms‐Tuohy et al, ; Valdez‐Moreno et al, ) and the catfish in Chesapeake Bay, USA (Aguilar et al, ). One study measured the consumption of fishery discards by birds, revealing that, although breeding success was higher in populations with access to discarded fish, mortality could also be enhanced by the increased interacting with fishing vessels (McInnes, Jarman, et al, ).…”
Section: Important New Research Avenues From Diet Studies Using Dna Mmentioning
confidence: 99%